2023
DOI: 10.3390/jcm12062438
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Insomnia Severity and Health Outcomes in the United States

Abstract: Little is known about the associations between insomnia severity, insomnia symptoms, and key health outcomes. Using 2020 United States National Health and Wellness Survey (NHWS) data, we conducted a retrospective, cross-sectional analysis to determine the associations between insomnia severity and a number of health outcomes germane to patients (health-related quality of life (HRQoL), employers and government (workplace productivity), and healthcare payers (healthcare resource utilization (HCRU)). The Insomnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is interesting to highlight the deterioration in quality of life within the control group at 6 and 9 months. Insomnia directly impacts quality of life, as proven in various studies, such as those conducted by Taylor et al [73][74][75], who affirm that insomnia is associated with a worse general health state, negatively affecting one's self-perception. Zeithlhofer et al [76] also concluded the presence of a close connection between quality of life and insomnia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is interesting to highlight the deterioration in quality of life within the control group at 6 and 9 months. Insomnia directly impacts quality of life, as proven in various studies, such as those conducted by Taylor et al [73][74][75], who affirm that insomnia is associated with a worse general health state, negatively affecting one's self-perception. Zeithlhofer et al [76] also concluded the presence of a close connection between quality of life and insomnia.…”
Section: Discussionmentioning
confidence: 94%
“…If we delve into the analysis of quality of life based on the EQ-5D scale variables, which is a tool that has been used in various studies that evaluate insomnia [75,77,78] and has been utilised to measure the results of cognitive behavioural and psychoeducational interventions [19,61,79], we have observed that some variables improve significantly, but not all. These variables are Pain/Discomfort (p = 0.016) and Self-Care (p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that the gut-brain axis is dysregulated in relation to insomnia and that abnormalities in the gut microbiota can make the condition worse. To date, there have been few investigations into the relationship between intestinal flora and insomnia ( Qi et al., 2022 ; Bundgaard-Nielsen et al., 2023 ; Chalet et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%